ANALISIS DU PONT SYSTEM UNTUK MENILAI KINERJA KEUANGAN PT. MANDOM INDONESIA TBK PERIODE 2015-2019 - Benny Rojeston Marnaek Nainggolan; Kristina Melimina Finowa’a; Tetty Tiurma Uli Sipahutar (LPPM Universitas Nias Raya, 2024)
The scope of this research is a study of financial statement analysis using Du Pont System analysis to assess the financial performance of PT. Mandom Indonesia Tbk. The purpose of this research is to assess the financial performance of PT. Mandom Indonesia Tbk using Du Pont System during the period 2015-2019. The analytical method used is the Du Pont System method, an analysis that shows how the relationship between NPM, TATO and EM in determining ROI and ROE. Based on the calculation results, it is concluded that the financial performance analyzed using the Du Pont System during 2015-2019 is in a state of fluctuation and is not good. This is indicated by the fluctuating and decreasing ROE. The decrease in ROE is caused by a decrease in the NPM and TATO ratios which are a result of burden inefficiency, total asset inefficiency and total debt inefficiency.